Welcome by the Rector of Vilnius University at the International Research Conference “Francysk Skaryna and the Renaissance Book Culture. Skaryna’s Little Traveller‘s Book Turns 500” - Petrauskas, Rimvydas (Knygotyra, 2023)
Dear Colleagues, This year marks the celebration of a remarkable event in the cultural history of the Grand Duchy of Lithuania – the establishment of the printing house of Francysk Skaryna in Vilnius and the beginning of book printing in Lithuania. The printing house was established in the capital of the Grand Duchy of Lithuania, and, although it worked only for a few years, it still marked the beginning of a great history. As the preface to the programme of this conference beautifully states, “The Grand Duchy of Lithuania became part of the Gutenberg galaxy.” Historians, philologists, and art historians will spend several days discussing this historical event, examining its cultural context and its consequences from different perspectives. I would especially like to emphasize the multi-disciplinary approach of this conference which is bound to enable us to share and deepen our knowledge. It is clear that the Francysk Skaryna printing house is a phenomenon of the multicultural and multi-confessional tradition of the Grand Duchy. Skaryna came from the Belarusian lands of the Grand Duchy of Lithuania, and studied in Padua before working between Prague and Vilnius, where he eventually went on to publish Orthodox books. The title of the first book he published was The Little Traveller’s Book. And this title aptly reflects the mobility of Skaryna himself as well as many other literary people of the time, although the intended meaning of the title is somewhat different. The beginning of the 16th century was a significant period in the history of the Grand Duchy of Lithuania. The codification of Law (the First Statute of Lithuania), the first complete history of Lithuania, and the first original works of fiction were written at that time. In this context, the establishment of the Skaryna printing house reflects both the growing political consciousness of the contemporary society, as well as its literacy. Let us turn to the present day. I’m very happy to welcome you to Vilnius. We have all missed such in-person conferences. Still, we must not forget the current political situation. We need to be responsible in our behaviour with history. And we urgently need to explore what the foundations of a new European and global policy should be. All this thinking must be done in a rational, focused, knowledge-based and contextual manner. And that is what we, the academics, can provide for societies consumed by the anxiety of war, manipulated by the media and biases of propaganda. And that is how we, the academic community, show how relevant we are to the external world. Just as Skaryna recognized the benefits of printing texts for his society, we all recognize the value of disseminating accurate information and our duty to combat misinformation. However, speaking truth to power and standing up for what is right requires courage. In this way, I would like to extend a special welcome to our colleagues from Belarus and Ukraine. Many of them, for various reasons, are unable to continue in their regular positions, and some of them have to call themselves ‘independent researchers’ because they have lost their jobs because of their views. We welcome you to Lithuania and Vilnius and are always ready to support you. I would like to finish my speech by wishing you a productive and meaningful conference and a pleasant time in Vilnius. Next year, we shall celebrate the 700th anniversary of our capital city. In 1323, Gediminas, the Grand Duke of Lithuania, invited people from all over Europe to come to Vilnius and settle down for peaceful trade and business. I am happy to vouch that our commitment to open international cooperation continues to stand firm. Thank you very much for your attention.